To find the 9th term of the arithmetic sequence using the explicit formula \( A_n = 14 + (n - 1) \cdot 12 \), we need to substitute \( n = 9 \) into the formula.
Let's calculate it step by step:
-
Substitute \( n = 9 \): \[ A_9 = 14 + (9 - 1) \cdot 12 \]
-
Simplify \( (9 - 1) \): \[ (9 - 1) = 8 \]
-
Now, multiply by 12: \[ 8 \cdot 12 = 96 \]
-
Finally, add 14: \[ A_9 = 14 + 96 = 110 \]
The calculated 9th term \( A_9 = 110 \).
It appears none of the answer choices provided in your response correspond to 110. Please double-check the options or provide additional information as needed.